2013
DOI: 10.3233/prm-140257
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy patients discovered dead during sleep: Experience from a comprehensive tertiary pediatric center

Abstract: OBJECTIVES: It is not uncommon for children with cerebral palsy (CP) to be discovered dead during sleep (DDDS); however, the factors associated with this pattern of mortality remain unknown. The current study aims to describe the mortality associated with children with CP from a single, tertiary care center who were DDDS. METHODS: A retrospective (case-only) design to examine proportionate mortality and patient characteristics and comorbidities that may be related to children DDDS between 1993 and 2011. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A study done by Newman et al of 173 school age children with cerebral palsy attending the Central Remedial Clinic in Dublin, Ireland, found that 39 (22.3%) had a pathological total sleep score [ 3 ].Sleep disturbance in patients with cerebral palsy may increase morbidity. Karatas et al reviewed the records on the deaths of 177 cerebral palsy and found that 19(10.7%) of them were discovered dead during sleep (DDDS) at home [ 4 ]. Children with cerebral palsy may have multiple risk factors for sleep disturbance because of the nature of their primary brain injury [ 5 ].Various factors contributing to sleep disorders have been proposed including mental retardation [ 6 ],visual impairment [ 7 ],seizures [ 8 ],anti-epileptic medications [ 9 ],obstructive sleep apnea [ 10 ],restricted movements due to contractures, spasticity and motor impairment [ 3 ],pain [ 11 ]due to spasticity, dental caries, use of orthoses, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Newman et al of 173 school age children with cerebral palsy attending the Central Remedial Clinic in Dublin, Ireland, found that 39 (22.3%) had a pathological total sleep score [ 3 ].Sleep disturbance in patients with cerebral palsy may increase morbidity. Karatas et al reviewed the records on the deaths of 177 cerebral palsy and found that 19(10.7%) of them were discovered dead during sleep (DDDS) at home [ 4 ]. Children with cerebral palsy may have multiple risk factors for sleep disturbance because of the nature of their primary brain injury [ 5 ].Various factors contributing to sleep disorders have been proposed including mental retardation [ 6 ],visual impairment [ 7 ],seizures [ 8 ],anti-epileptic medications [ 9 ],obstructive sleep apnea [ 10 ],restricted movements due to contractures, spasticity and motor impairment [ 3 ],pain [ 11 ]due to spasticity, dental caries, use of orthoses, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In an Australian cerebral palsy registry, respiratory problems were very common, with daily cough or wheeze in 58%, obstructive sleep apnoea in 10%, cough with drinking in 40% and abnormalities on clinical pulmonary exam in around 20% [ 9 ]. Children with cerebral palsy have an increased risk of sudden death during sleep and most of these patients have a cluster of respiratory problems such as recurrent aspiration pneumonia, chronic bronchitis and (nocturnal) respiratory insufficiency [ 10 ]. Pneumonia may disproportionally contribute to mortality in cerebral palsy and some data suggest that pneumonia was responsible for 40% of all deaths [ 9 ].…”
Section: Epidemiologymentioning
confidence: 99%